Analisis makna tersembunyi di balik video klip Bigbang “Still Life” dalam perspektif semiotika Roland Barthes - Fahira, Hafizhah Almas (Maliki Interdisciplinary Journal, 2023)
Music is a medium used by some people to communicate with others through tones and lyrics combined with various beautiful instruments and depictions of stories through a video clip. Through music videos a person is able to express emotions and thoughts that he cannot express with mere words. Through this research, the writer tries to convey the hidden meanings behind this video clip. By using a descriptive qualitative method approach and collecting data by means of observation, data exploration, and documentation which are then analyzed using Roland Barthes’ semiotic theory which includes denotation, connotation, and myth meanings. Where in this study shows the results of the analysis in the form of three main points namely a brief explanation regarding Bigbang’s profile, an analysis of the denotative and connotative meanings of the 15 scenes in Bigbang’s "Still Life" video clip, along with an analysis of the myths that developed regarding the presence of this music video. The conclusion of this study is that Bigbang’s video clip "Still Life" refers to a message about the meaning of life and the impression of separation which means to always be ready to welcome new beginnings because life is like seasons that keep changing and are always in different phases as different as human life.